Early provision of oropharyngeal colostrum leads to sustained breast milk feedings in preterm infants - Ruth Snyder; Aimee Herdt; Nancy Mejias-Cepeda; John Ladino; Kathryn Crowley; Philip Levy (Elsevier, 2017)
Background: Oropharyngeal colostrum (OC) application strategies have been shown to be feasible and safe for very low birth weight (VLBW) infants. Evidence to support the nutritional and clinical advantages of OC care remains somewhat theoretical. The objectives of this study were to a) confirm the feasibility and safety of OC application in preterm infants and b) determine if OC application is associated with improved nutritional and clinical outcomes from birth to discharge. We hypothesized that OC application in the first few days would promote sustained breast milk feedings through discharge. Methods: An observational longitudinal study was conducted in 133 VLBW infants during 2013â14, after an OC protocol was adopted. Maternal and infant characteristics, infant vital signs during administration, nutritional outcomes, and common neonatal morbidities were assessed and compared to 85 age- and weight-matched VLBW infants from a retrospective control cohort from 2012, prior to the implementation of the OC protocol. Results: There were no adverse events or changes in vital signs during the application of OC. VLBW infants who received OC continued to receive the majority of their enteral feeds from human breast milk at six 6 of age and through discharge (pÂ <Â 0.01). There was no difference in maternal characteristics known to affect breast milk production, and rates of common neonatal morbidities were statistically similar between groups. Conclusion: OC application for VLBW infants is safe and practical in a neonatal intensive care unit setting and is associated with increased rates of breast milk feeding. Key Words: oropharyngeal colostrum, infant nutrition, prematurity, neonatology